Leading for gold: social identity leadership processes at the London 2012 Olympic Games - Slater, M. J.; Barker, J. B.; Coffee, P.; Jones, M. V. (Qualitative Research in Sport, Exercise and Health, 2015)
This paper adopted a social identity approach to explore the media data of leadership figures at the London 2012 Olympic Games. Media data in the form of interviews, speeches/team announcements, and blog posts from leaders integral to the London 2012 Olympic Games were analysed from 100 days prior to, during, and for 30 days following, the Olympic Games. Leaders included Lord Seb Coe, Andy Hunt, and performance directors of TeamGB athletics (Charles van Commenee), cycling (Sir David Brailsford), rowing (David Tanner) and swimming (Michael Scott). An inductive and deductive thematic analysis identified five higher order themes: creation of team identities, team values, team vision, performance consequences and `we` achieved. The analysis makes a contribution to extant leadership literature by highlighting novel contextually relevant themes surrounding leadership at the London 2012 Olympic Games. Thus, opportunities for future research and application are outlined.